Becoming Modern Muslim: New Emerging Trends of Islamic Schools in Yogyakarta - Lukis Alam (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2017)
The growth of Islamic school education in Indonesia has been phenomenally rapid, affecting a new emergence of Islamic school in the country. In few years ago we only recognised two models of Islamic education: pesantren (boarding school) and madrasah (conventional Islamic school). The current wave of Islamic schools in Indonesia attempts to integrate secular education and religious curriculum in one curriculum. Interestingly, the teachings in these schools reinvigorate modern Muslim parents to get their children enrolled in those institutions. Nowadays urban society demands educational institution that effectively equips the students with ability in handling the challenges of rapid globalisation. Furthermore, Muslim parents enthusiastically welcome to this new trend of Islamic school in Indonesia. Uncontrolled social interaction, moral and ethical decadence have risen concerns amongst parents about their children future. Hence, this challenge prompts them to think of solution for their children in near future. The establishment of educational institution which is being able to respond to such global problems is necessary. With a blend of modern and religious curricula, Islamic school is aspired to provide skills to children so that they are capable of facing the consequences of globalisation. This system is also expected to generate a solid religious morality as a platform for moral development for children to prevent them from getting drifted into negative consequences of globalisation. Accordingly, modern Islamic school is developed in response to these issues. This paper is in attempt to examine the presence of Islamic schools in Yogyakarta. Characteristics of each school will be scrutinized. The paper will focus on the discussion of their characteristics, aiming for responding to social concerns and parent expectation for their children to be able to survive amidst the turmoil of modernity as well as for the school in being able to bridge the Islamic way of life with global problems.